Expedited Arbitration: A Study of Outcomes and Duration - Webb, Shannon; Wagar, Terry (Relations industrielles / Industrial Relations, 2018)
In both academic and practitioner communities, there is an increased concern related to the time-consuming nature of the traditional labour arbitration system in Canada. The arbitration process was initially instituted to combat the delays and costs experienced in the courts. This study addresses the gap in the scientific literature by considering these ongoing concerns.Many Canadian jurisdictions offer the parties an opportunity to expedite the arbitration process pursuant to applicable legislation. However, despite the opportunity to accelerate the process, there appears to be a reluctance to use the expedited arbitration system. We performed content analysis on over 550 Canadian expedited and traditional labour arbitration cases. The case sample was limited to termination cases. We studied and compared delay at multiple times during the arbitration process, including the delay to the hearing, delay to the arbitration award, and total delay. Furthermore, we studied the case outcome; specifically, whether the grievance was granted or denied and adopted an ordered analysis to investigate differences in case outcomes.Our results support the perception that there is a difference in the expediency of expedited arbitration cases in comparison with traditional arbitration cases. The results also show that the outcomes of dismissal cases, decided in the expedited system, do not significantly differ from the traditional arbitration system. The findings suggest that there are statutorily available opportunities for the parties to accelerate the arbitration process without compromising the results.